COST AND TIME ANALYSIS USING EARNED VALUE METHOD IN ADMINISTRATION BUILDING CONTRUCTION PROJECT AT POLIJE CAMPUS - Irniawan, Dodik; Oetomo, Wateno; Marleno, Risma (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2023)
Implementation of construction projects often faces delays in work completion. Delays in project completion that exceed the time limit specified in the contract cause losses both from the contractor as the executor and the assignor. Project implementers pay more attention to the cost aspects incurred and often ignore the time control of project implementation so that project implementation often experiences delays in work. The purpose of this study is to analyze the time efficiency carried out by the provider from the beginning of the work, during monitoring, to the end of the project implementation. And estimate how much it costs from the start of work, when monitoring until the project is completed using the Earned Value Method. From the analysis, results and discussion of the Bondowoso Polije Campus Administration Building project, it can be concluded that the project work time exceeds 2,543 weeks for the total work and will experience a loss of Rp 393,323,318.10 from the reduction of the total contract minus the total financing. Therefore, the construction management proposes to shift the work schedule to work that does not require the achievement of the main construction. In addition, the contractor should communicate to the assignor of the Administration Building project to increase the duration of the administrative building construction project work. And participate in finding alternative suppliers of the main material without having to wait for the vendor to get the material needed.